PENGARUH MODEL PEMBELAJARAN INDEX CARD MATCH TERHADAP HASIL BELAJAR SISWA KELAS V SD NEGERI 1 PACING WEDI KLATEN TAHUN PELAJARAN 2022/2023 - Aditya Arianto Widodo (Bajang Institute, 2023)
The background of this research is the low social studies learning outcomes of Class V SD Negeri 1 Pacing Wedi Klaten, the lack of active participation of students in the learning process in class, and the learning process is still teacher-centered, so there is a need for alternative learning models to overcome this. The formulation of the problem in this research is: is there any effect of applying the index card match learning method to student learning outcomes in social studies class V SD Negeri 1 Pacing Wedi Klaten in the 2022/2023 academic year and the purpose of this study is to determine the effect of applying the index method to learning card match on social studies learning outcomes for fifth grade students at SD Negeri 1 Pacing Wedi Klaten for the 2022/2023 academic year. The research method used is descriptive quantitative, a method that describes and describes the relationship between several variables with one another. To obtain data using experimental learning techniques, tests, observations or observations, and documentation. Based on the application of the index card match learning method, the results of understanding were categorized as good with the effectiveness of using the method. This is based on increased student activity such as student attitudes during learning, student collaboration, seriousness, skills and understanding of learning concepts during learning. The application of the index card match learning method increases almost 100% above the KKM, which shows that the application of the index card match learning method can improve learning outcomes. There is a significant influence on the application of the index card match learning method to the learning outcomes of fifth grade students in the social studies subject at SD Negeri 1 Pacing Wedi Klaten in the 2022/2023 academic year. The correlation value of 0.786 is positive between the X and Y variables with a coefficient of determination of 61.8%. If the regression line equation is made, it is Y = 79.244 + 0.349X